2021
DOI: 10.1007/s12553-021-00609-8
|View full text |Cite
|
Sign up to set email alerts
|

Current limitations to identify covid-19 using artificial intelligence with chest x-ray imaging (part ii). The shortcut learning problem

Abstract: Since the outbreak of the COVID-19 pandemic, computer vision researchers have been working on automatic identification of this disease using radiological images. The results achieved by automatic classification methods far exceed those of human specialists, with sensitivity as high as 100% being reported. However, prestigious radiology societies have stated that the use of this type of imaging alone is not recommended as a diagnostic method. According to some experts the patterns presented in these images are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…By separating the training and validation data from each center, we were able to show that our multimodal approach achieved high performance and generalized well to data that are characteristically different from the training dataset and have not been seen before. It has been shown that previous imaging-based AI models for COVID-19 prognostication may be inadequate for real clinical usage [35,36]. The major reason for this was the lack of external validation data.…”
Section: Discussionmentioning
confidence: 99%
“…By separating the training and validation data from each center, we were able to show that our multimodal approach achieved high performance and generalized well to data that are characteristically different from the training dataset and have not been seen before. It has been shown that previous imaging-based AI models for COVID-19 prognostication may be inadequate for real clinical usage [35,36]. The major reason for this was the lack of external validation data.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the approaches developed for the classification of the CXR images relay on global features [2], [11], [12], [14]. However, these features may not accurately represent the complex nature of CXR images [22]. It should be verified when working with medical images, especially when the model's accuracy is very high [13], [21], the reasons why algorithms perform so well to prevent developing algorithms which base their decision on confounding factors rather then medical pathology.…”
Section: Introductionmentioning
confidence: 99%
“…They create a map of lung areas important for COVID-19 detection and claim a production-ready solution. Considering the need for a critical approach to chest classification and analysis of biases [23], [22], [20], we carry out further research into the analysis of the deep learning model decisions using the COVIDx dataset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one hand, there may be visible lesions on CT that are not visible on CXR images. On the other, among CXR and CT scans, CXR images are interesting because they have a lower associated cost, are faster to acquire, and are more widely available [Pereira et al 2020], [López-Cabrera et al 2021]. In this work, we focus our attention on the CXR images.…”
Section: Introductionmentioning
confidence: 99%